INTEGRASI PENDIDIKAN KRISTEN DANTEOLOGI UNTUK MEMBANGUN GENERASI BERIMAN DI ERA DIGITAL - Marindy Shani Kala'; Bua La'bi', Yeyen Tandi Lete, Lindayani, Sumitra Bontong (CV. ADIBA AISHA AMIRA, 2025)
The digital era brings new challenges in building a generation of believers, especially in a society rooted in Christian values. The integration of Christian education and theology is a strategic approach to answer this challenge. This article discusses the importance of combining the principles of Christian education with theological doctrine to strengthen the character, faith and spiritual values of the younger generation. Through this approach, students are not only given a deep theological understanding, but are also equipped with critical and ethical thinking skills that are relevant to technological developments. This integration includes Bible-based teaching, the application of Christian values in the use of technology, and the development of faith- based learning communities. This article emphasizes the need for collaboration between churches, schools, and families to create an educational environment that supports the growth of faith in the midst of an ever-growing digital era.